2011
DOI: 10.1242/jcs.079731
|View full text |Cite
|
Sign up to set email alerts
|

The Stil protein regulates centrosome integrity and mitosis through suppression of Chfr

Abstract: SummaryStil (Sil, SCL/TAL1 interrupting locus) is a cytosolic and centrosomal protein expressed in proliferating cells that is required for mouse and zebrafish neural development and is mutated in familial microcephaly. Recently the Drosophila melanogaster ortholog of Stil was found to be important for centriole duplication. Consistent with this finding, we report here that mouse embryonic fibroblasts lacking Stil are characterized by slow growth, low mitotic index and absence of clear centrosomes. We hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 41 publications
(46 reference statements)
3
57
2
Order By: Relevance
“…The same authors also reported mitotic spindle defects in HeLa cells, as confirmed in our present study. Similarly, STIL-deficient mouse embryonic fibroblasts were shown to display defects in cell cycle progression (Castiel et al, 2011). STIL-knockout (Stil -/-) mice die at embryonic day 10.5, with prominent axial midline defects and randomized cardiac looping, consistent with a block in Sonic hedgehog (Shh) signaling (Izraeli et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors also reported mitotic spindle defects in HeLa cells, as confirmed in our present study. Similarly, STIL-deficient mouse embryonic fibroblasts were shown to display defects in cell cycle progression (Castiel et al, 2011). STIL-knockout (Stil -/-) mice die at embryonic day 10.5, with prominent axial midline defects and randomized cardiac looping, consistent with a block in Sonic hedgehog (Shh) signaling (Izraeli et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, STIL expression was reported to be high in lung cancer (Erez et al, 2004) and most interestingly, mutations in STIL were recently shown to cause primary microcephaly (Kumar et al, 2009). Additional studies point to a possible role for STIL in cell proliferation, mitotic regulation and centrosome integrity (Izraeli et al, 1997;Campaner et al, 2005;Erez et al, 2007;Castiel et al, 2011), but the precise function of this protein remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, patients with microcephaly associated with osteodysplastic primordial dwarfism (MOPD), such as Meier-Gorlin syndrome, have mutations affecting subunits of the origin recognition complex, which is loaded onto chromatin at DNA origins before the S phase of mitosis to license replication; in conjunction with additional components CDC6, CDT1, and MCM2 -7, it forms the prereplication complex, which initiates DNA replication . Other genes that, when mutated, result in microcephaly include those involved in microtubule formation (TUBA1A, TUBB2B, TUBB3, TUBG1) (Poirier et al , 2012Cushion et al 2013), those coding for microtubule-associated proteins (DYNC1H, KIF5C, NDE1) (McKenney et al 2010;Alkuraya et al 2011;Bakircioglu et al 2011;Poirier et al 2013), those involved in spindle organization and positioning (ASPM) (Desir et al 2008;Passemard et al 2009), those regulating centriole length (CENPJ) (Tang et al 2009;Al-Dosari et al 2010) or centrosome integrity (STIL) (Castiel et al 2011), those that repair genomic defects and regulate genomic integrity (CEP152) (Kalay et al 2011), and many others involved in the very complex process of cell replication. By a combination of clinical characteristics (Mahmood et al 2011), imaging characteristics ( Fig.…”
Section: Microcephaliesmentioning
confidence: 99%
“…Note that each peptide appears twice since it exists in duplicate, which verifies the reliability of the results. The interaction between STIL and CHFR was previously demonstrated at the protein level 13,14 . The peptide array screening revealed 7 CHFR-derived peptides that bound STIL IDR, residues 500-650 (Figure 3 …”
Section: Representative Resultsmentioning
confidence: 77%
“…It controls normal cell division and cell proliferation 13,[15][16][17][18][19] . STIL interacts with several proteins 18,20,21 , and most of the interactions occur through its central part, which is an intrinsically disordered region (IDR) 14 .…”
Section: Representative Resultsmentioning
confidence: 99%